2013
DOI: 10.4274/jcrpe.1136
|View full text |Cite
|
Sign up to set email alerts
|

L-thyroxine Stabilizes Autoimmune Inflammatory Process in Euthyroid Nongoitrous Children with Hashimoto’s Thyroiditis and Type 1 Diabetes Mellitus

Abstract: Objective: To investigate if L-thyroxine (T4) treatment may influence the clinical course of autoimmune thyroiditis (AIT) or prevent progression to subclinical or overt hypothyroidism in euthyroid nongoitrous pediatric patients with type 1 diabetes mellitus (T1DM) and AIT.Methods: The study was performed in four Polish pediatric diabetes centers. Of 330 children with T1DM and AIT followed between 2008 and 2012, 101 received L-T4 and 160 underwent clinical observation for 24 months. Thyroid stimulating hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to the authors, the lower TNF-α and IL-17 levels, which correlated with low vitamin D status, could be explained by the control of cytotoxicity by long-time treatment of HT. As stated by Korzeniowska et al [ 91 ], levothyroxine may contribute to stabilizing the inflammatory process in HT. In a study by Wencai Ke et al [ 92 ], serum 25(OH)D levels were not associated with IL-4, IL-17, and TNF-α in newly diagnosed or treated patients with HT.…”
Section: Role Of Vitamin D In the Immunopathology Of Hashimoto’s Thyr...mentioning
confidence: 93%
“…According to the authors, the lower TNF-α and IL-17 levels, which correlated with low vitamin D status, could be explained by the control of cytotoxicity by long-time treatment of HT. As stated by Korzeniowska et al [ 91 ], levothyroxine may contribute to stabilizing the inflammatory process in HT. In a study by Wencai Ke et al [ 92 ], serum 25(OH)D levels were not associated with IL-4, IL-17, and TNF-α in newly diagnosed or treated patients with HT.…”
Section: Role Of Vitamin D In the Immunopathology Of Hashimoto’s Thyr...mentioning
confidence: 93%
“…In general, the optimum equilibration temperature of CPE was 15 to 20 C higher than the cloud point temperature of the surfactant. 14 Considering the low cloud point temperature (22 to 30 C) of TX-114, we tested the effect of the equilibration temperature in the range from 40 to 80 C. The extraction efficiency increased with increasing the temperature in the range from 40 to 68 C and then decreased above 68 C (Fig. 6).…”
Section: Mechanism Of Double Cloud Point Extraction For Uranylmentioning
confidence: 99%
“…12 A novel double cloud point extraction (dCPE) was developed recently that has played important roles in the eld of environment science and is becoming increasingly popular due to the simplicity of operation, rapidity of extraction, low cost, environmental friendliness, and high enrichment factors. 13,14 To the best of our knowledge, no study to date has been reported on the determination of uranyl based on the dCPE technique. In this investigation, we integrate the advantages of photo-catalytic RF and dCPE technology for detecting trace amounts of uranyl.…”
Section: Introductionmentioning
confidence: 99%